Sensitivity of the corn (Zea mays L.) crop to different periods of controlled water deficit - Sáez-Cigarruista, Ana; Morales-Guevara, Donaldo; Gordón-Mendoza, Román; Jaén-Villarreal, Jorge; Franco-Barrera, Jorge; Ramos-Manzané, Francisco (Agronomía Mesoamericana, 2024)
Introduction. Corn is one of the oldest known food grains. With climate change and frequent and severe droughts, the water available in the soil will be considerably reduced. Water deficit affects maize crop development to varying degrees, and sensitivity to this stress varies at different development stages. Objective. To identify the phenological stages most sensitive to water deficit in maize. Materials and methods. The experiment was conducted during two growing seasons in 2020 and 2021 in El Ejido, Los Santos province, Panama, under semi-controlled conditions in the greenhouse facilities of the Instituto Coronel Segundo de Villarreal. The commercial corn hybrid ADV-9293 was used and agronomic management was carried out according to the recommendations of the Institute for Agricultural Innovation of Panamá (IDIAP). Plant height, leaf length and width, stem diameter, biomass and yield components, such as number of rows per ear, number of grains per row and 100-grain mass, were determined throughout the crop cycle. Soil moisture was also determined by the gravimetric method. Water deficit at different stages was generated by drought simulation. Results. The grain yields of the control were higher than the different treatments evaluated with 12.83 t ha-1, followed by the treatment with grain filling stress with 10.31 t ha-1. Two periods were determined to be more sensitive to water deficit; these were the stages from 20 to 35 and 40 to 55 days after planting. Water deficit in the different phenological stages of the crop had a negative impact on the relative chlorophyll content. Conclusion. The pre-flowering and flowering stages were more sensitive to water deficiency in maize.